To the history of the Russian vagrancy XVII–XIX centuries - Shliakov, Aleksei (Przegląd Wschodnioeuropejski, 2018)
In the following article analysis of vagabondism in Russia is being made, based on sources from literature, journalism and the Holy Father. The particular qualities of the Church, temporal powers, and common society members’ attitudes towards vagabondism are being viewed. The periods of the romanticizing of vagabondism in the history of Russia are being described as well as periods when vagabondism was subjected to social exclusion. A gradual transition of the perception of vagabondism from the field of Christian traditional humility and mercy to a social field which inflicts responsibility for one’s behavior on the subject of vagabondism is explored. Methods and manners of charity for vagabonds and the poor are being viewed as well as the imperative measures and sanctions of the struggle against mendicity and vagabondism in various historical periods. The classifications of vagabonds, offered by Russian thinkers, are being researched since they allow us to distinguish between the needy and those who use the image of a vagabond for their own profit and who speculate on Christian feelings. Generally, the authors come to a conclusion that unlike Western Europe, where vagabondism was banned and where vagabonds were punished severely, the attitude towards vagabonds in pre-revolutionary Russia was based on the orthodox values and included humanity and mercifulness.